REVITALIZING LOCAL WISDOM: EFFORTS TO REDUCE TENSION AMONG BELIEVERS - Hasse J. (Al-Albab, 2014)
This article aims to show that through the strengthening of local wisdom, apathy toward the existence of other groups can be avoided to form a better order of life. Concern about the condition of the Indonesian people that are considered to have less appreciation for the other groups, in particular against certain religious groups has triggered the author to explore these issues and to respond to the concern. This nation, in fact, has a mechanism which has proved capable of reducing and even quelling the potential of conflict in a multi-cultural society. It is often called local mechanism. Although it has local characteristics, but if taken to a higher level, then the mechanism will generate new institutions for creating a broader harmony. This brief article showed that the existing local wisdom could create a harmonious relationship among the Bugis community though they have different faith. This is part of their commitment to practicing the noble values of local wisdom so that differences of identity (religion) are not a deterrent in building good relations, but in deed serve as a medium that acts as a reinforcement to the existing order. Keywords: Revitalizing, Local wisdom, Social Relations.